Second Generation Nitrogen Doped Titania Nanoparticles: A Comprehensive Electronic and Microstructural Picture. Issue 12 (5th December 2014) - Spadavecchia, Francesca; Ceotto, Michele; Presti, Leonardo Lo; Aieta, Chiara; Biraghi, Iolanda; Meroni, Daniela; Ardizzone, Silvia; Cappelletti, Giuseppe
Abstract A state‐of‐the‐art overview of N‐dopant characterizations in nano‐TiO2 second‐generation photocatalysts is provided. The related literature is very rich and sometimes offers contrasting interpretations. Here we critically discuss up‐to‐date literature results and our own findings, as retrieved by several experimental (BET, HR‐TEM, XPS, DRS, HR‐XRPD, EXAFS, electrochemical tools) and theoretical (periodic DFT) techniques. Our intent is to pull together outcomes from very different and complementary sources to make an as much as possible coherent picture of the morphological, electrochemical and electronic properties of N‐TiO2 materials. It is commonly accepted that critical issues to be considered in the design of high‐performing N‐TiO2 photocatalysts are synthetic strategy, defect concentration and chemical nature of the lattice point defects. We focus on the latter two issues, with emphasis on sol‐gel prepared materials, according to the specific area of expertise of our group. The problem of the chemical nature of guest N species into the lattice is crucial, as substitutional (Ns) or interstitial (Ni) nitrogen place their valence states just above the valence band or deeper into the band gap. Overall, we show how synergism among experimental and theoretical techniques is decisive to disentangle structural, electronic and morphological effects in complex N‐doped TiO2 matrices.